Report on the II Scientific Congress of Martial Arts and Combat Sports, por Vítor Rosa - Vítor Rosa (Universidad de León, 2012)
This text resumes the communications and posters presented at the II Scientific Congress of Martial Arts and Combat Sports (CCMACS), held on 16 and 17 May 2009, in the Polytechnic Institute of Viseu (Portugal). In an environment characterized by a significant international presence and a wide variety of thematics issues presented, a total of 38 communications and 13 posters were exposed, organized in six major areas: 1) Study object, research and systematic of martial arts and combat sports (MA&CS), 2) Physical, technique and tactics dimensions of MA&CS; 3) Pedagogical, psychological and tactics dimensions of MA&CS; 4) Socio-cultural and philosophical dimensions of MA&CS; 5) The martial arts in Portugal; and 6) Posters. The results of the Congress allow us to affirm the growing interest of the MA&CS as a subject of academic study, and to certify the importance of this type of event to the knowledge and build of networks among researchers in the MA&CS.